An assessment of the implementation of the Early Reading Initiative (ERI) of the Zimbabwean Primary school: A Case Study of the Bumburwi cluster Gweru District. - Saiden, Thondhlana; Raramai, Thondhlana (Advances in Social Sciences Research Journal, 2018)
The Early Reading Initiative (ERI) in Zimbabwean primary Schools was necessitated by early learning gaps that negatively affect performance at grade 7 and O level in Zimbabwe which is attributed to incompetency in reading by learners inherited from early grades. Reading competency is a fundamental skill which should be systematically organised for learners to master the necessary pre-reading skills during early learning grades and throughout the primary school years. Zimbabwe is presently implementing a Science Technology Engineering and Mathematics curriculum reading ability is crucial to the implementation of this curriculum. The study was aimed at establishing the implementation of the components of the ERI programme. The study was necessitated by need to establish implementation problem areas so that corrective actions could be undertaken. The sample consisted of Early Childhood Development teachers 7 (ECD), 6 grade one teachers and 5 grade 2 teachers who were purposively chosen. A qualitative paradigm was adopted. A case study design was employed. Lesson observations, in- depth interviews and documents analysis were undertaken. The major findings were that components for the programme were appropriate, most of the components were not excellently implemented and the amount of support given to teachers in the implementation of the programme was quite adequate. Some of the recommendations were that, individual components without fidelity of implementation were to be attended to through staff development sessions, individual teachers with specific problems in implementing certain components to be identified as individual assistance is to be offered to them at school or cluster level.